Ethics in finance - Boatright, John Raymond, 1941- (Malden, MA : Blackwell Pub., 2008)
"This second edition of the ground-breaking Ethics in Finance is an up-to-date, valuable addition to the emerging field of finance ethics. Citing examples of the scandals that have shaken public confidence in Wall Street, John R. Boatright explains the importance of ethics in the operation of financial markets and institutions and in the conduct of finance professionals." "Focusing on standards of fairness in market transactions and the duties of fiduciaries and agents in financial relationships, the author introduces a broad range of practical issues related to financial markets, the financial services industry, investment decision making, and corporate financial management. In addition to the topics considered in the first edition, including unethical sales practices, insider trading, the abuse of bankruptcy, and hostile takeovers, the second edition of Ethics in Finance has a broadened scope, incorporating new discussions of issues in mutual funds, conflict of interest, and the financial theory of the firm." "This timely and comprehensive book provides an analysis of ethical issues in finance, suitable for students of finance and business ethics as well as anyone involved in financial activities."--Jacket.
Financial ethics : an overview : The need for ethics in finance ; Ethics and financial markets ; The financial services industry ; Individuals in organizations -- Theoretical perspectives in finance : Equity and efficiency ; Fiduciaries, agents, and professionals ; Agency theory ; Conflict of interest -- Ethical issues in financial services : Sales practices ; Churning, twisting, and flipping ; Arbitration ; Personal trading ; Mutual funds -- Ethical issues in investment decisions : Bank lending practices ; Socially responsible investing ; Relationship investing ; Investment and the new finance -- Ethics in financial markets : Insider and program trading ; The ethics of bankruptcy ; Hostile takeovers -- The financial theory of the firm : Traditional theories ; The contractual theory ; The objective of the firm ; The stakeholder challenge.
Includes bibliographical references and index.
Keywords: Business ethics; Finance -- Moral and ethical aspects